A Study to Assess Genuineness of Obstetrics / Gynecological Patients Coming or Being Referred to Medical College Hospital in Southern District of Rajasthan - Sharma, C P; Sharma, Shalabh; Kumar, Arun; Jain, Chetan K (National Journal of Community Medicine, 2013)
Background: In recent years it has been observed that medical college hospitals have been over burdened, bed occupancy has doubled and hospitals are finding it difficult to handle this increased patient load, putting enormous pressure on already scarce manpower and infrastructure resources. Objective: To assess the reasons of increased indoor patient registrations specially focusing on the department of obstetrics and gynecology of RNT Medical College, Udaipur. Material and methods: 300 patients in different Wards of the department of obstetrics and gynecology and only those coming from outside municipal limits of Udaipur were interrogated through a predesigned structured questionnaire and responses of treating doctors were also taken over a period of 1 month. Results: Total 300 admitted patients were included in the study. Participants belong to 17-44 years age group (mean age 29.06±12.06 years). Majority of 172(57.3%) patients sought services of this hospital for some genuine gynecological problems, 77(25.66%) for pregnancy with complication .About 147(49%) patients had come to the tertiary level hospital for non availability of assured, round the clock specialist services in their own areas. Fear of complications 172(57.33%) and lack of faith and confidence in locally available medical officer 122(40.66%) have been the major reason for not availing services at periphery. Conclusion: In view of the above findings there is urgent need to strengthen services and infrastructure in tertiary level hospitals to cope up with the increased workload.